2013
DOI: 10.1186/1999-3110-54-54
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis among three Taiwan-specific Gentiana species and Chinese medicinal plant Gentiana scabra

Abstract: BackgroundThe root of Gentiana scabra is commonly known as Longdan in Chinese herbal medicines and has been used in the treatment of inflammation, anorexia, indigestion and gastric infections for over 2000 years. High market demand had made G. scabra (GS) plants not to be the only source of Longdan in China, other Gentiana spp., G. triflora, G. manshurica and G. rigescens, were also recognized as Longdan in China now.ResultsIn this study, we identified three Taiwan-specific Gentiana spp., G. davidii var. formo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Interestingly, the TFC/TPC ratios in the studied root samples of yellow gentian were in the range of 0.15 to 0.17, indicating low percentage rate of TFC vs. TPC. Huang et al (2013) also reported the low TFC/TPC ratios in six different Gentiana spp. root samples.…”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, the TFC/TPC ratios in the studied root samples of yellow gentian were in the range of 0.15 to 0.17, indicating low percentage rate of TFC vs. TPC. Huang et al (2013) also reported the low TFC/TPC ratios in six different Gentiana spp. root samples.…”
Section: Resultsmentioning
confidence: 92%
“…punctulata) from Taiwan and compared with that in G. scabra. The swertiamarin content in G. davidii and G. scabra was reported to be substantially higher, 2.66 and 2.52mg/g, respectively (Huang et al 2013). Aberham et al (2007) reported the swertiamarin content in 12 commercial samples of G. lutea root to be between 0.21% and 0.45%.…”
Section: Identification and Estimation Of Amarogentin Swertiamarin An...mentioning
confidence: 99%
“…Gentian is a traditional Chinese medicine that is known to possess various pharmacological properties, including hepatoprotective, anti-inflammatory, analgesic, antitumor, stomachic, diuretic and antiviral effects [ 1 , 2 , 3 ]. Due to its rich medicinal properties, gentian has maintained a stable and long-lasting demand in the market.…”
Section: Introductionmentioning
confidence: 99%